Comparing strategies for grinding itabirite iron ores in autogenous and semi-autogenous pilot-scale mills. (15th March 2021) - Rodrigues, Armando F.d.V.; Delboni Jr, Homero; Powell, Malcolm S.; Tavares, Luis Marcelo
Graphical abstract: Highlights: 625 tons of four itabirite types were collected for bench and pilot scale tests. AG/SAG milling is technically feasible for grinding itabirites. Closed single-stage circuit was the most attractive in terms of grinding efficiency. Pebble crushing increased throughput and energy efficiency. AG/SAG is more efficient than crushing and ball mill circuit for 3 of the 4 samples. Abstract: High grade iron ore resources are becoming depleted in Brazil, with relatively low-grade ores requiring more intensive comminution for proper liberation of iron minerals, followed by upgrading. Comminution circuits that have been frequently used in the Brazilian iron ore industry in preparation of high-grade iron ores consist of multiple crushing stages followed by ball milling and are known for being highly complex and capital-intensive installations. This work assesses the potential suitability of autogenous (AG) and semi-autogenous (SAG) milling through an extensive pilot plant campaign carried out with itabirite iron ores. The effects of ore type, feed size distribution, circuit configuration (open or closed-circuit and two-stage or single-stage), mode of grinding (AG or SAG), ball load, use of pebble crushing as well as of full secondary pre-crushing have been investigated. The results demonstrate both the technical feasibility and energy efficiency of such an alternative for itabirite comminution circuits.